2012
DOI: 10.1371/journal.pone.0036713
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FGFR4 Inhibits Hepatocellular Carcinoma in Preclinical Mouse Models

Abstract: The fibroblast growth factor (FGF)-FGF receptor (FGFR) signaling system plays critical roles in a variety of normal developmental and physiological processes. It is also well documented that dysregulation of FGF-FGFR signaling may have important roles in tumor development and progression. The FGFR4–FGF19 signaling axis has been implicated in the development of hepatocellular carcinomas (HCCs) in mice, and potentially in humans. In this study, we demonstrate that FGFR4 is required for hepatocarcinogenesis; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
175
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(178 citation statements)
references
References 31 publications
3
175
0
Order By: Relevance
“…In this article, we show that one such variant, M70, fully retains the biologic activity of FGF19 in regulating bile acid homeostasis while devoid of tumorigenicity. Notably, we found that M70 binds to and activates FGFR4, which is assumed to mediate FGF19-associated tumorigenicity (13,16). Mechanistically, we show that FGF19 stimulates tumor progression by activating the STAT3 pathway, an activity completely eliminated by M70.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In this article, we show that one such variant, M70, fully retains the biologic activity of FGF19 in regulating bile acid homeostasis while devoid of tumorigenicity. Notably, we found that M70 binds to and activates FGFR4, which is assumed to mediate FGF19-associated tumorigenicity (13,16). Mechanistically, we show that FGF19 stimulates tumor progression by activating the STAT3 pathway, an activity completely eliminated by M70.…”
Section: Introductionmentioning
confidence: 63%
“…Transgenic mice with ectopic expression of FGF19 in skeletal muscle develop HCC at the age of 10-to 12-month-old (11). This tumorigenic activity is thought to be mediated by the liver-enriched FGFR4, because inactivation of FGFR4 via gene knockout or by a neutralizing antibody reduces tumor burden in FGF19 transgenic mice (12,13). Therefore, targeting the FGF19-FGFR4 pathway has the potential for treating HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Both inhibitors exhibited excellent potency against typical cancer cell lines harboring FGFR amplifications or mutations, including the FGFR4-dependent cell line A2780, which is resistant to many current FGFR inhibitors. FGFR4 has been reported to play a very important role in metastasis, drug resistance, and poor prognosis (23,(68)(69)(70); therefore FIIN-2 and FIIN-3, with good FGFR4 potency, show promising potential for application in many FGFR-dependent cancer types such as breast cancer (63,71) and hepatocellular carcinoma (72,73). In addition, they are capable of overcoming the valine-to-methionine gatekeeper mutation in H2077 and H1581 cell lines, although similar mutations found in patients' specimens have been demonstrated experimentally to confer resistance to the leading clinical FGFR inhibitors (19,48,50).…”
Section: Discussionmentioning
confidence: 99%
“…Several different mAb have been developed to target components of the FGF-FGFR axis: GP369 (Bai et al, 2010), GAL-FR21 (Zhao et al, 2010), GAL-FR22 (Inokuchi et al, 2015), GAL-F2 , MFGR1877S (Fauvel and Yasri, 2014), hLD1.vb (Bumbaca et al, 2011), FP-1039(Marshall et al, 2011, R3Mab (French et al, 2012), PRO-001 (French et al, 2012), 1A6 (Pai et al, 2008) and LD1 (French et al, 2012). Two main mechanisms of action have been considered; either blocking ligand binding (trap-ligand) or preventing receptor dimerization.…”
Section: Antibodies Against Fgfs and Fgfrs And Fgf-ligand Trapmentioning
confidence: 99%